Biosocial portrait of a patient with COVID-19 - O. V. Kryvoviaz; I. K. Shcherba; Т. І. Voitenko; L. V. Kremenska (The State Expert Center of the Ministry of Health of Ukraine, 2021)
The world has been in a pandemic for more than a year. During this time, 155 million people worldwide fell ill, including 3,24 million people who died. In Ukraine, 2,15 million cases were recorded, including 47 thousand deaths. Establishing the biosocial characteristics of patients will make it possible to predict the probability of infection and the subsequent course of COVID-19. The aim of the study was to establish correlations of social, biological and medical characteristics of patients with severity of COVID-19. The study was based on information and analytical database, which contained personal data of 294 students of the Pharmacy Department of National Pirogov Memorial Medical University, Vinnytsya and members of their families who were ill with COVID-19 for the period March 2020-March 2021. The questionnaire contained 24 questions related to gender and age structure, compliance with quarantine norms, frequency of visits to public places, the size of the work or training team, the course of the disease and the presence of comorbidities, blood groups of patients with COVID-19. The study used sociological and medical-statistical methods. According to the survey, it can be concluded that the patient with COVID-19 is in the vast majority of cases a woman (75%) with the second blood group (50%), who attends work or study groups (74%) or has family members who attend them (17%). The patient with severe and very severe course or complications after COVID-19, according to our study, is mainly a woman over 50 years old, with second (44%) or third (31%) group of blood. She is actively attends small social groups or has members families who visit them (74% and 17%, respectively, have concomitant pathologies of the cardiovascular system (59%) or metabolic disorders (22.7%). Students of the Pharmacy Department of National Pirogov Memorial Medical University, Vinnytsya were infected with SARS-CoV-2, are mostly boys and girls aged 19-23 (89%); they are studying in the second (19%), third (36%) and fourth (34%) course, have a second (41%) or the third (31%) blood group. Usually with mild (39%) and moderate (47%) course of coronavirus disease, socially active (74%) or have family members who frequently visit public places, work or study groups (17%).